A Examining Fuzzy Partial Metric Space and Associated Outcomes - Pathak, Renu P.; Gore, Rohini R. (Communications in Mathematics and Applications, 2025)
Using the concept of a PM space with fuzzy, it gives idea of a FPMS in this paper. A point’s self-distance in partial metric space does not always equal to zero. Ordinary metric is a subset of partial metric. Additionally, also define continuous t-norms. Partial fuzzy contraction mapping is defined here. It also demonstrates that, in certain circumstances, the complete partial metric space has a common fixed point through use of contraction mapping. Relevant examples are used as provide results.
Keywords: Fixed point theorem; Fuzzy sets; Fuzzy metric space; Partial metric space